Decreasing ventromedial prefrontal cortex deactivation in risky decision making after simulated microgravity: effects of −6° head-down tilt bed rest - Rao, Li-Lin; Zhou, Yuan; Liang, Zhu-Yuan; Rao, Henyi; Zheng, Rui; Sun, Yan; Tan, Cheng; Xiao, Yi; Tian, Zhi-Qiang; Chen, Xiao-Ping; Wang, Chun-Hui; Bai, Yan-Qiang; et al. (Frontiers in Behavioral Neuroscience, 2014)
Space is characterized by risk and uncertainty. As humans play an important role in long-duration space missions, the ability to make risky decisions effectively is important for astronauts who spend extended time periods in space. The present study used the Balloon Analog Risk Task to conduct both behavioral and fMRI experiments to evaluate the effects of simulated microgravity on individuals’ risk-taking behavior and the neural basis of the effect. The results showed that participants’ risk-taking behavior was not affected by bed rest. However, we found that the ventromedial prefrontal cortex (VMPFC) showed less deactivation after bed rest and that the VMPFC activation in the active choice condition showed no significant difference between the win outcome and the loss outcome after bed rest, although its activation was significantly greater in the win outcome than in the loss outcome before bed rest. These results suggested that the participants showed a decreased level of value calculation after the bed rest. Our findings can contribute to a better understanding of the effect of microgravity on individual higher-level cognitive functioning.